2021
DOI: 10.3390/ijerph18147279
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metal Concentrations and Associations with Pulmonary Function among Children with Asthma in Chicago, Illinois

Abstract: Individuals living in areas with the potential for elevated metal exposure from industrial sources may have reduced pulmonary function. We evaluated cross-sectional associations of toenail concentrations of 17 metals within a community area of residence and asthma control in 75 children, and pulmonary function measures [forced expiratory volume in one second (FEV1; liters), forced vital capacity (FVC; liters), FEV1 to FVC ratio (FEV1:FVC), and mid-exhalation forced expiratory flow rate (FEF 25–75%; liters/seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…A study by Zierold et al examined residents who lived within 10 miles (16 kmmuch larger than our study area) from a coal ash storage facility and used geospatial analysis to confirm that the participants with high iron (Fe), Al, and silicon (Si) (which loaded together in nails of children near coal ash storage facility, using PCA) lived closer to the coal ash storage facility . A study of 39 children in Chicago observed higher toenail levels of Cd, Co, Fe, Mn, and V in children living near an industrial corridor than in children in a comparison community . Future studies can build on this current study by examining metal concentrations in people near an oil drilling site and using a larger study radius or a control area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Zierold et al examined residents who lived within 10 miles (16 kmmuch larger than our study area) from a coal ash storage facility and used geospatial analysis to confirm that the participants with high iron (Fe), Al, and silicon (Si) (which loaded together in nails of children near coal ash storage facility, using PCA) lived closer to the coal ash storage facility . A study of 39 children in Chicago observed higher toenail levels of Cd, Co, Fe, Mn, and V in children living near an industrial corridor than in children in a comparison community . Future studies can build on this current study by examining metal concentrations in people near an oil drilling site and using a larger study radius or a control area.…”
Section: Discussionmentioning
confidence: 99%
“… 74 A study of 39 children in Chicago observed higher toenail levels of Cd, Co, Fe, Mn, and V in children living near an industrial corridor than in children in a comparison community. 75 Future studies can build on this current study by examining metal concentrations in people near an oil drilling site and using a larger study radius or a control area.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has suggested metals are harmful to adults' lung function, particularly for occupational workers (Wu et al, 2022). Despite evidence that childhood periods are a critical time window for lung development and likely a vulnerable period for metal exposure, there is limited study on the childhood population, with only seven relevant studies to our knowledge (Feng et al, 2022;Leung et al, 2013;Madrigal et al, 2021;Madrigal et al, 2018;Pan et al, 2020;Zeng et al, 2017;Zheng et al, 2013). And six out of seven of the previous researches looked at no more than ve blood/urine metal constituents simultaneously (Feng et al, 2022;Leung et al, 2013;Madrigal et al, 2018;Pan et al, 2020;Zeng et al, 2017;Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…And six out of seven of the previous researches looked at no more than ve blood/urine metal constituents simultaneously (Feng et al, 2022;Leung et al, 2013;Madrigal et al, 2018;Pan et al, 2020;Zeng et al, 2017;Zheng et al, 2013). Only in a recently published study among asthmatic children, 17 toenail metals were analyzed, in which different blood metals were found to be negatively associated with varying pulmonary function variables in single-pollutant models (Madrigal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-recognized that exposure to an excessive amount of vanadium can cause damage and metabolic changes in multiple systems including respiratory system (16,17). Recent epidemiological studies have indicated that vanadium exposure may be associated with impaired pulmonary function parameters and reduced asthma control among children with preexisting asthma (18). Studies with mouse models have suggested that exposure to vanadium pentoxide (V 2 O 5 ) gives rise to airway smooth muscle thickening, airway mucous cell metaplasia, and an increased proliferation of peribronchiolar myofibroblasts, thereby leading to the development of airway fibrosis and remodeling (19).…”
Section: Introductionmentioning
confidence: 99%